The Anthem Companion to Pierre Bourdieu - Robbins, Derek (Anthem Press, 2016)
The Anthem Companion to Pierre Bourdieu' provides an introduction to the French sociologist's thought and an evaluation of the international significance of his work from a range of national perspectives. The contributions in the companion investigate the applicability of Bourdieu's theories and concepts in diverse sociopolitical contexts and consider the ways they can be said to possess universal validity. In examining Bourdieu on his own philosophical terms, this companion contributes to the general debate about the effects of the transnational and transcultural transfer of concepts generated in the West.